2020
DOI: 10.5014/ajot.2020.035287
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Jail-Based Occupational Therapy Transition and Integration Services Program for Community Reentry

Abstract: Importance: Transition and integration reentry services continue to grow in carceral settings; however, related provision of occupational therapy is limited. Objective: To examine the implementation fidelity of an occupational therapy–administered interprofessional reentry program initiated in an urban jail. Design: Retrospective, mixed quantitative and qualitative design. Setting: Community-based reentry services provided prerelease in a Midwestern urban jail and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…However, only a few transitional programs such as support for transitional housing, and job placement / vocational training exist that aim to fill such gaps (Bowman & Ely, 2020; Fox, 2012; Peled-Laskov et al, 2019). Jaegers et al (2020) implemented a jail-based transitional program, and the findings were congruent with our participants’ personal accounts which point to the need for improved access to and resources within transitional programs for ex-offenders. This study holds the potential to inform advancements of transitional programs in the future by providing personalized perspectives of barriers and facilitators to successful transitions from the prison system.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, only a few transitional programs such as support for transitional housing, and job placement / vocational training exist that aim to fill such gaps (Bowman & Ely, 2020; Fox, 2012; Peled-Laskov et al, 2019). Jaegers et al (2020) implemented a jail-based transitional program, and the findings were congruent with our participants’ personal accounts which point to the need for improved access to and resources within transitional programs for ex-offenders. This study holds the potential to inform advancements of transitional programs in the future by providing personalized perspectives of barriers and facilitators to successful transitions from the prison system.…”
Section: Discussionsupporting
confidence: 79%
“…Studies related to ex-offender community reintegration have been conducted in different countries, which include Australia (van Dooren et al, 2011), Canada (Brown, 2004; Falardeau et al, 2015; McKendy & Ricciardelli, 2020), Norway (Larsen et al, 2019), South Africa (Chikadzi, 2017; de Wet, 2005; Soeker et al, 2013), Ukraine (Morozova et al, 2013), and the United States (Davis et al, 2013; Garland et al, 2011; Jaegers et al, 2020). However, studies on ex-offender community reintegration conducted in the United States mainly focused on specific transitional programs and concluded with barriers and facilitators founded on socio-economical levels (Jaegers et al, 2020). Few studies have investigated the post-prison transition between the once incarcerated minority individuals and their community in the United States.…”
mentioning
confidence: 99%
“…Furthermore, meetings with a variety of stakeholders with lived experience with justice involvement voiced their needs for reentry planning (also described as reintegration or community transition preparation) with the second author. These discussions led to research projects informed by the voices of the officers and with stakeholders with lived experience [15,19]. Findings from these studies identified the gap in addressing meaningful work roles among officers and jail or prison residents and led to the development of the SLU Transformative Justice Initiative (TJI).…”
Section: Observation 2: Correctional Officer Healthmentioning
confidence: 99%
“…The program is unique for working with individuals in jail and continuing services after release to the community. To determine program feasibility, we performed a process evaluation to track occurrence and duration of OT activities, participant attendance, completion of homework, and barriers and facilitators (gathered during weekly OT team meetings) [19].…”
Section: Observation 3: Reentry Process Evaluationmentioning
confidence: 99%
“…Occupational Therapists can support these transitions, particularly in circumstances where the transition may be challenging, or supports are required to negotiate the next phase. Examples include supporting school transitions for autistic students (Cremin et al , 2017), guiding the work-to-retirement transition (Eagers et al , 2022), negotiating the transition to work for people with Intellectual Disability (Jaegers et al , 2020) or interventions to support the transition out of homelessness (Marshall et al , 2021) to name but a few.…”
mentioning
confidence: 99%